Transcription termination in the archaebacterium Sulfolobus: signal structures and linkage to transcription initiation. - Reiter, W D (1988)
The precise map positions were determined for the 3'-termini of five transcripts of the Sulfolobus virus-like particle SSV1. In all cases analyzed, these 3'-termini mapped immediately downstream of a sequence TTTTTYT which was part of a pyrimidine-rich region of 16-19 nucleotides length. No correlation was evident between the position of the 3'-termini and possible secondary structures within the RNA. In two cases, the 3'-termini of SSV1 transcripts mapped in the immediate vicinity of transcriptional initiation sites suggesting that transcription termination can be linked to the re-initiation of RNA synthesis.